1999
DOI: 10.1021/jo9818430
|View full text |Cite
|
Sign up to set email alerts
|

σ-Dative and π-Backdative Phenyl Cation−Dinitrogen Interactions and Opposing Sign Reaction Constants in Dual Substituent Parameter Relations

Abstract: For the overwhelming number of reactions studied with dual substituent parameter treatments, the ratio of the reaction constants rho(R)/rho(F) = lambda is positive and close to unity. Dediazoniations are prominent representatives of the very few unusual reactions for which dual substituent parameter (DSP) relations yield reaction constants of opposing sign. To understand this exceptional behavior, we have studied with ab initio methods the energetic, structural, and electronic relaxations along the unimolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 61 publications
5
22
0
1
Order By: Relevance
“…Following the valence bond model (Lewis-Kekulé), one would expect the charge to be localized on the N 2 moiety. In contrast, Glaser et al 10 have shown that the C-N bonding is more appropriately described by a synergistic interplay between s-dative C N 2 and p-backdative C ! N 2 bonding with the phenyl ring carrying most of the positive charge.…”
mentioning
confidence: 93%
“…Following the valence bond model (Lewis-Kekulé), one would expect the charge to be localized on the N 2 moiety. In contrast, Glaser et al 10 have shown that the C-N bonding is more appropriately described by a synergistic interplay between s-dative C N 2 and p-backdative C ! N 2 bonding with the phenyl ring carrying most of the positive charge.…”
mentioning
confidence: 93%
“…Furthermore, the chosen arene had to be highly tolerant towards as many chemical reactions as possible. In the already mentioned theoretical studies of Glaser, [10] and from experimental data [11] it was shown that pchloro-substituted diazonium ions are very stable. For that reason we chose 2-chloro-5-aminobenzyl alcohol (2) as starting material for the formation of a stable diazonium ion on solid support (Scheme 1).…”
mentioning
confidence: 92%
“…This can be achieved by the in situ diazotization of aryl amines followed by reductive grafting [31]. The electron density model described the bonding in diazonium by synergistic N→C σ-bonding and C→N π-back-bonding [32][33][34]. A stabilizing effect for the C-N bond includes the formation of charge-transfer complexes, metal-based anion, and coordination [35][36][37].…”
Section: Introductionmentioning
confidence: 99%